Sugar transfer of nanomaterials and flexible electrodes - Tianzeng Hong; Tianze Shen; Junlong Yang; Yichen Sun; Jianming Zhang; Haiyang Pan; Ying Hong; Yan Wang; Shuo Chen; Yue Zhao; Chuan Fei Guo (International Journal of Smart and Nano Materials, 2020)
Nanomaterials with various dimensionalities (e.g., nanowires, nanofilms, two-dimensional materials, and three-dimensional nanostructures) have shown great potential in the recent development of flexible electronics. Conventionally, organic solvents are inevitable while integrating nanomaterials onto flexible substrates, where polymer mediator-assisted transfer techniques are involved. This often damages the flexible substrate and thus hamper the large-scale application of nanomaterials. Here we report a method using water-soluble sugar as a mediator to facilely transfer nanomaterials onto rigid or flexible substrates. This method requires no organic solvent during transfer. More importantly, the morphology and properties of transferred nanomaterials, such as shape, microstructure, resistivity, and transmittance are well preserved on the target substrate. We believe that this universal and rapid transfer method can greatly advance the applications of nanomaterials in the field of flexible devices and beyond.